THE TAXONOMY OF SAKURA AS A LIFE PORTRAIT OF LIWA PEOPLE - I Wayan Mustika (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Sakura performing arts in Liwa, West Lampung regency, has several varieties of characters in accordance with types of performance. Sakura, viewed from its appearance, has been made with a lot of varieties of style and costume which is in line with the performers’ development of science and knowledge. It can also be defined as a traditional game using many varieties of Sakura characters. Sakura consists of two types: (a) Sakura Kamak and (b) Sakura Helau. Sakura Kamak was in the past used as a ritual for worshipping ancestral spirits described to have ugly-looking faces wearing shabby clothes. Sakura means a mask and Kamak means ugly, dirty, or old. Thus, Sakura Kamak is identifiable from its face shapes and ugly, dirty, ragged, and muddy dress. Meanwhile, Sakura Helauhas a good-looking face and nice dress. The Sakura types are named according to their costumes, dance movement styles, and behavior of the Sakura performers, rather dance movement styles, and behavior of the Sakura performers, rather than the expressions or appearances.